The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s43045-020-00029-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of anxiety and depression among substance use disorder patients: a case-control study

Abstract: Background Several evidences from epidemiologic and treatment studies indicate that anxiety disorders, depression, and substance use disorders commonly co-occur, and the interaction is multifaceted and variable. Epidemiological studies and investigations within clinical substance abuse populations have found an association between anxiety disorders, depression, and substance use disorders. Results The mean age was 28.1 ± 6.5 years. The majority belonged to the moderate socioeconomic status (52%). Substance us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 29 publications
4
21
1
5
Order By: Relevance
“…Studies showed that people who suffer from depression and anxiety are often addicted to any kind of stimulants [46]. If students become addicted, he or she will develop a strong interest in stimulants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that people who suffer from depression and anxiety are often addicted to any kind of stimulants [46]. If students become addicted, he or she will develop a strong interest in stimulants.…”
Section: Discussionmentioning
confidence: 99%
“…40(33.3%) patients were unemployed and 80(66.7%) were employed. These findings were comparable to the some previous studies [16][17][18] . The latest research shows that most opioid addicts are poly drug addicts.…”
Section: Discussionsupporting
confidence: 93%
“…Dual disorder patients suffer higher rates of psychiatric hospitalizations (25), suicide attempts (26), more social problems and delinquent behaviors (24,27), worse QOL (28)(29)(30), lower social consultation, and lesser use of social support (31), compared with those without comorbidity. A great body of research has indicated that substance use can exacerbate depression (27,32,33). The presence of an MDD increases the likelihood of developing an SUD and vice versa (34), although familial and genetic factors seem to be two risk factors for comorbidity of SUD and MDD (SUD + MDD) (35).…”
Section: Introductionmentioning
confidence: 99%